2023
DOI: 10.4018/978-1-6684-6334-5.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Migration From Georgia and Ukraine in the Context of Russian Aggression

Abstract: The authors examine migration as one of the urgent problems of the modern global world. The phenomenon of migration has been indispensable for human history, culture, and civilizations, the causes of which have always existed and still exist. All sorts of wars, confrontations/conflicts turn a group of society into refugees and push them to migrate from the source of conflict to neighboring or distant countries. Also, the underlying causes, such as social, political, economic, and other factors, which are inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The military intervention of the Russian Federation in Ukraine became the reaction catalyst for the operational organization of various aid in European countries [4]. The Ukrainian case showed that the recover resilience is difficult process and implemented due to international and national stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…The military intervention of the Russian Federation in Ukraine became the reaction catalyst for the operational organization of various aid in European countries [4]. The Ukrainian case showed that the recover resilience is difficult process and implemented due to international and national stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…It involves using skills with economic tools to advance a country's economic, trade and strategic goals. Hence, economic relations are a tool (economic strategy) for improving economic standards, stimulating trade, and supporting domestic companies (Abuseridze et al, 2022). In this regard, countries as Ukraine, seeking a competitive advantage in the international arena cannot ignore the possibilities of economic cooperation and pursue a closed foreign economic policy.…”
Section: Introductionmentioning
confidence: 99%